Active ingredients in Chinese medicines promoting blood circulation as Na＋/K＋-ATPase inhibitors - Chen, Ronald JY; Jinn, Tzyy-rong; Chen, Yi-ching; Chung, Tse-yu; Yang, Wei-hung; Tzen, Jason TC (Acta pharmacologica Sinica, 2011)
The positive inotropic effect of cardiac glycosides lies in their reversible inhibition on the membrane-bound Na＋/K＋-ATPase in human myocardium. Steroid-like compounds containing a core structure similar to cardiac glycosides are found in many Chinese medicines conventionally used for promoting blood circulation. Some of them are demonstrated to be Na＋/K＋-ATPase inhibitors and thus putatively responsible for their therapeutic effects via the same molecular mechanism as cardiac glycosides. On the other hand, magnesium lithospermate B of danshen is also proposed to exert its cardiac therapeutic effect by effectively inhibiting Na＋/K＋-ATPase. Theoretical modeling suggests that the number of hydrogen bonds and the strength of hydrophobic interaction between the effective ingredients of various medicines and residues around the binding pocket of Na＋/K＋-ATPase are crucial for the inhibitory potency of these active ingredients. Ginsenosides, the active ingredients in ginseng and sanqi, substantially inhibit Na＋/K＋-ATPase when sugar moieties are attached only to the C-3 position of their steroid-like structure, equivalent to the sugar position in cardiac glycosides. Their inhibitory potency is abolished, however, when sugar moieties are linked to C-6 or C-20 position of the steroid nucleus; presumably, these sugar attachments lead to steric hindrance for the entrance of ginsenosides into the binding pocket of Na＋/K＋-ATPase. Neuroprotective effects of cardiac glycosides, several steroid-like compounds, and magnesium lithospermate B against ischemic stroke have been accordingly observed in a cortical brain slice-based assay model, and cumulative data support that effective inhibitors of Na＋/K＋-ATPase in the brain could be potential drugs for the treatment of ischemic stroke.